2006
DOI: 10.1002/bmc.635
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous estimation of six anti‐diabetic drugs—glibenclamide, gliclazide, glipizide, pioglitazone, repaglinide and rosiglitazone: development of a novel HPLC method for use in the analysis of pharmaceutical formulations and its application to human plasma assay

Abstract: This paper describes a convenient method for the separation and simultaneous determination of six anti-diabetic drugs viz., glibenclamide (GLB), gliclazide (GLC), glipizide (GLZ), pioglitazone (PGL), repaglinide (RPG) and rosiglitazone (RGL) in pharmaceutical formulations. Also, the assay has been shown applied to support quantification of the six anti-diabetic drugs in human plasma. The analytes were either injected directly onto the column after suitable dilution (pharmaceutical formulation analysis) or a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 8 publications
1
40
0
2
Order By: Relevance
“…Several HPLC methods have been reported in the literature for quantitative determination of MET alone [4] or in combination with other drugs in tablets [5][6][7], human serum and other biological fluids [8][9]. Similarly, a few HPLC methods have been reported for the quantitative determination of REPA in tablets alone or in combination with other drugs [10][11][12], and in human serum and other biological fluids [13,14]. Only one UV spectroscopic method has been reported for the simultaneous determination of these compounds, which, however, lacks stabilityindicating nature [15].…”
Section: Introductionmentioning
confidence: 99%
“…Several HPLC methods have been reported in the literature for quantitative determination of MET alone [4] or in combination with other drugs in tablets [5][6][7], human serum and other biological fluids [8][9]. Similarly, a few HPLC methods have been reported for the quantitative determination of REPA in tablets alone or in combination with other drugs [10][11][12], and in human serum and other biological fluids [13,14]. Only one UV spectroscopic method has been reported for the simultaneous determination of these compounds, which, however, lacks stabilityindicating nature [15].…”
Section: Introductionmentioning
confidence: 99%
“…Solutions were pre-treated and maintained at 37 ± 0.5 ºC and the paddles were set at 75 rpm. At appropriate time intervals (10,20,30,45 and 60 min), 5 mL samples were collected, filtered through 0.45 μ filter paper and analyzed for drug content by HPLC at 230 nm. An equal volume of fresh medium was added to the test solution to maintain constant volumes.…”
Section: In Vitro Dissolution Testmentioning
confidence: 99%
“…13 Different research has reported that glibenclamide has a low bioavailability, which is attributed to its poor dissolution properties. [14][15][16] Different methods have been reported to determine glibenclamide levels in various biological fluids, such as plasma 17,18 and serum, 19 in pharmaceutical formulation analyses [20][21][22] or in simultaneous determination of anti-diabetic drugs. 23 Our objectives were to formulate calcium-alginate beads containing glibenclamide by ionotropic gelation, characterize the resulting microparticles, evaluate the release characteristics of glibenclamide loaded calcium-alginate beads in an in vitro dissolution test, and compare it with two commercially available trademarks (Daonil ® and Glibetab ® ).…”
Section: Introductionmentioning
confidence: 99%
“…Several assay techniques have been described for quantitative determination of glibenclamide in biological fluids; these include procedures based on high performance liquid chromatography (HPLC) [10][11][12][13][14][15][16][17][18] , fluorometry 19 , radioimmunoassay [20][21][22] and gas chromatography 23 . A few reports deal with the analysis of the drug in these dosage forms; such procedures include: micellar electrokinetic capillary chromatography 24 , RP-HPLC 15,25 , fluorometry 26 , TLC-UV spectrophotometry 27 , derivative spectrophotometry 28 , UV spectrophotometry 29 and colorimetry 30 .…”
Section: Introductionmentioning
confidence: 99%
“…A few reports deal with the analysis of the drug in these dosage forms; such procedures include: micellar electrokinetic capillary chromatography 24 , RP-HPLC 15,25 , fluorometry 26 , TLC-UV spectrophotometry 27 , derivative spectrophotometry 28 , UV spectrophotometry 29 and colorimetry 30 . At the present time there is no dissolution test for glibenclamide tablets reported in any pharmacopeia.…”
Section: Introductionmentioning
confidence: 99%